2023
DOI: 10.1097/hpc.0000000000000327
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Toxicity Associated With Immune Checkpoint Inhibitor Therapy: A Comprehensive Review

Abstract: Immune checkpoint inhibitors (ICIs), a significant breakthrough treatment of cancer, exert their function through enhancing the immune system’s ability to recognize and attack cancer cells. However, these revolutionary cancer treatments have been associated with a range of immune-related adverse effects, including cardiovascular toxicity. The most commonly reported cardiovascular toxicities associated with ICIs are myocarditis, pericarditis, arrhythmias, and vasculitis. These cardiovascular manifestations are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 115 publications
(192 reference statements)
0
4
0
Order By: Relevance
“…A consequence of reactivating immune surveillance is a myriad of irAEs, including cardiotoxicity. The pathophysiology of these adverse events is poorly understood, but one proposed mechanism suggests cross-reactivity related to molecular mimicry [ 4 ]. Examples of cardiotoxicity include cardiac arrest, heart failure, myocarditis, and pericardial disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A consequence of reactivating immune surveillance is a myriad of irAEs, including cardiotoxicity. The pathophysiology of these adverse events is poorly understood, but one proposed mechanism suggests cross-reactivity related to molecular mimicry [ 4 ]. Examples of cardiotoxicity include cardiac arrest, heart failure, myocarditis, and pericardial disease.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of cardiotoxicity include cardiac arrest, heart failure, myocarditis, and pericardial disease. Although pericardial disease is especially rare, occurring at a rate of 0.36%, the associated mortality rate is high accounting for anywhere from 13-21% of fatalities [4][5][6][7]. The time course for ICI-related pericardial disease is usually within 30 days of treatment [8], presenting as dyspnea, chest pain, and hemodynamic instability [8,9], with dyspnea being the most common symptom [10].…”
Section: Discussionmentioning
confidence: 99%
“…These T cells destroy malignant cells; however, they may also target healthy cardiac tissue. Another proposed mechanism suggests that molecular mimicry induces cardiac tissue autoimmunity [4]. Cardiotoxic irAEs presenting as pericardial disease are uncommon, representing approximately 0.36% of reported toxicities [5].…”
Section: Discussionmentioning
confidence: 99%
“…Based on prior research, the majority of toxicities occur within one year; however, reports have shown that they can also occur years after initiation of ICIs [3]. Due to this, several studies recommend performing routine cardiac surveillance in patients receiving ICIs, including a baseline cardiovascular assessment [3,4].…”
Section: Table 2: Prior Cases Of Nivolumab And/or Ipilimumab-related ...mentioning
confidence: 99%